2021
DOI: 10.1111/apa.16107
|View full text |Cite
|
Sign up to set email alerts
|

How to manage irritable bowel syndrome in children

Abstract: Aim This paper discusses the risk factors and management of paediatric irritable bowel syndrome (IBS), with a focus on the role of the gastrointestinal microbiome. Methods English articles of interest published in PubMed and Google Scholar were searched using subject heading and keywords of interest. Results Only few randomised controlled trials on the management of IBS in children have been published. The vast majority of these intervention trials target to change the composition of the gastrointestinal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Эта передача сигналов может также модулировать нисходящую регуляцию моторики, секреции и передачи сигналов кишечника и мозга [13]. Открытие оси «кишечникмозг -микробиом» обозначило в качестве мишени терапии в лечении ФРОП коррекцию микробиоты [14,15]. Наряду с перечисленными выше механизмами, передача сигналов осуществляется также с помощью опиоидных рецепторов [16], которые принадлежат к суперсемейству семиспиральных трансмембранных рецепторов, связанных с G-белком (GPCR) [17].…”
Section: Gastroenterologyunclassified
“…Эта передача сигналов может также модулировать нисходящую регуляцию моторики, секреции и передачи сигналов кишечника и мозга [13]. Открытие оси «кишечникмозг -микробиом» обозначило в качестве мишени терапии в лечении ФРОП коррекцию микробиоты [14,15]. Наряду с перечисленными выше механизмами, передача сигналов осуществляется также с помощью опиоидных рецепторов [16], которые принадлежат к суперсемейству семиспиральных трансмембранных рецепторов, связанных с G-белком (GPCR) [17].…”
Section: Gastroenterologyunclassified
“…Furthermore, it is to be noted that the administration of prebiotics is not advised for the management of functional gastrointestinal disorders (FGIDs) in pediatric patients. A study conducted in a sample of 71 children by Levy et al, which administrated a prebiotic treatment consisting of 900 mg inulin twice daily for a duration of four weeks, did not yield significant results [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…The dose of the prebiotic used is a crucial factor in the treatment of IBS. Based on data obtained from four clinical trials conducted on adults, it has been observed that lower doses may be effective and high doses may have a negative impact on symptoms [ 43 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…A 2021 systematic review (23) on the different treatments of irritable bowel syndrome (IBS) identified only 1 trial that evaluated a synbiotic treatment (24). In this trial, a synbiotic treatment [ B. lactis B94 (5 × 10 9 CFU) and 900 mg inulin] was compared to a probiotic (5 × 10 9 CFU B. lactis B94) or a prebiotic (900 mg inulin) twice daily for 4 weeks, in 71 children with IBS (24).…”
Section: Management Of Gastrointestinal Conditions With Synbiotics In...mentioning
confidence: 99%